First thesaurus - Chatterton, Martin (London : Kingfisher, 2001)
An illustrated thesaurus containing over 100 key words accompanied by their synonyms, antonyms, and homonyms. Also includes example sentences to explain shades of meaning and games to play with words.
"Kingfisher First Thesaurus" is a helpful book for young kids to learn about words. It shows different ways to say the same thing and even words that mean the opposite. With colorful pictures and easy-to-understand examples, it makes building vocabulary fun and simple. It's a great tool for writing and speaking!
Keywords: Thesaurus